Implementation of Human Resource Management in the Modern Tourism development business "Le Hu Garden" - Devianti, Lilis; Hamdi , Edi; Anindita , Rina; Munandar , Agus (Innovative: Journal Of Social Science Research, 2025)
Natural tourism company Le Hu Garden Indonesia was created in 2016 in Deli Serdang, North Sumatra. Its goal is to provide the best tourist services by delighting all customers. Le Hu Garden is a natural attraction in North Sumatra's beautiful Deli Serdang district. Human resource management that follows trends is essential for organisational success. This research focused on HRM's influence in Le Hu Garden Company's success. Since many rising digital companies need IT professionals, Le Hu Garden may stay competitive by developing an efficient HRM strategy. Human Resource Management is used for hiring, staffing, professional development, salary, benefits, and labour relations. In the current natural tourist rivalry between Sumatra and Indonesia, a training centre is needed to produce people who understand technology for the company and its ecosystem and can generate money and new business. This study reveals that HRM is vital to company success and competition